Influence of sourdough on in vitro starch digestibility and predicted glycemic indices of gluten-free breads - Wolter, Anika; Hager, Anna-Sophie; Zannini, Emanuele; Arendt, Elke K (Food & function, 2014)
Gluten-free flours (buckwheat, quinoa, sorghum and teff) were fermented using obligate heterofermentative strain Weissella cibaria MG1 (Wc) and facultative heterofermentative Lactobacillus plantarum FST1.7 (Lp). Starch hydrolysis of breads with and without sourdough (controls) was analyzed in vitro using enzymatic digestion followed by dialysis (10-11 kDa). Hydrolysis indices as well as predicted glycemic indices (pGI) were calculated from reducing sugars released into the dialysate. Amounts of resistant starch (RS; % of total starch) were determined by enzymatic digestion. Upon sourdough addition, RS significantly decreased in buckwheat (Wc 1.28%, Lp 1.44%) and teff sourdough breads (Wc 0.87%, Lp 0.98%) in comparison to their controls (2.01% and 1.92%, respectively). However, no correlation was found with starch hydrolysis. Predicted GIs were reduced upon sourdough addition in wheat (ctrl 100; Wc 85; Lp 76) in comparison to control breads. This was not the case in most gluten-free breads with the exception of sorghum (ctrl 72; Lp 69) and teff sourdough breads (ctrl 74; Lp 68). In contrast, increased pGIs were found in quinoa (ctrl 95; Wc 106; Lp 103) and buckwheat sourdough breads (ctrl 80; Wc 89; Lp 86). Starch hydrolysis of gluten-free breads was analyzed in vitro using enzymatic digestion followed by dialysis. Evaluation of the formation of resistant starch, starch digestibility and predicted glycemic indices upon sourdough addition.